Assessing police treatment in Ecuador: the view of satisfied and disaffected female serious offenders. (3rd September 2018) - Romo Pérez, Andrea
Abstract: This empirical study examines procedural justice perceptions among 51 female serious offenders in Ecuador, with the aim of identifying differences between those women who were satisfied with law enforcement and those who were not. The results demonstrate that when women were treated with courtesy and respect, and their rights were acknowledged, they felt satisfied with the police, in a way that they did not give importance to the irregularities they observed while arrested and in custody. On the other hand, the majority of women participants were dissatisfied with the police. Their dissatisfaction with, and lack of trust in, the authorities affected their desire to cooperate with police activities. The study also demonstrates that, although the Ecuadorian police force has made considerable efforts in promoting citizens' trust during the last 7 years, corruption and illegal police conduct when dealing with offenders are far from uncommon.